The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1088/1612-2011/11/7/075601
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high repetition rate absorption spectroscopy with low noise supercontinuum radiation generated in an all-normal dispersion fibre

Abstract: We report use of a dispersed supercontinuum generated in an all-normal-dispersion fibre to record low-noise spectra from atmospheric molecules at least an order of magnitude faster than has been previously reported. Supercontinuum generation in standard, anomalous dispersion photonic-crystal fibres is inherently connected with large pulse-to-pulse fluctuations resulting in detrimental consequences for high resolution spectroscopy if temporal averaging is not permitted. Replacing the standard PCF with a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…While this is substantial, it is significantly less than observed for conventional, anomalous dispersion SC, where nonlinear amplification factors for shot noise in the order of 90 dB were measured [26]. With our time domain analysis we can therefore confirm previous observations made in the spectral domain that even in the incoherent regime, ANDi SC exhibit better noise properties than the corresponding conventional SC [44]. The decrease of noise amplification with increasing technical noise level observed in the long-pulse regime can be understood by the fact that the absolute noise levels are dominated by amplified quantum noise and therefore remain approximately constant with increasing technical noise.…”
Section: Noise Amplificationsupporting
confidence: 85%
See 2 more Smart Citations
“…While this is substantial, it is significantly less than observed for conventional, anomalous dispersion SC, where nonlinear amplification factors for shot noise in the order of 90 dB were measured [26]. With our time domain analysis we can therefore confirm previous observations made in the spectral domain that even in the incoherent regime, ANDi SC exhibit better noise properties than the corresponding conventional SC [44]. The decrease of noise amplification with increasing technical noise level observed in the long-pulse regime can be understood by the fact that the absolute noise levels are dominated by amplified quantum noise and therefore remain approximately constant with increasing technical noise.…”
Section: Noise Amplificationsupporting
confidence: 85%
“…Interestingly, previous studies of SC noise in the spectral domain have shown that even in the long-pulse incoherent regime, ANDi SC exhibit superior shot-to-shot stability compared to conventional, anomalous dispersion SC [44]. While ANDi SC spectra fluctuate in close correlation around a long-term mean, conventional SC exhibit more chaotic, radical fluctuations in which a single-shot spectrum does not resemble at all the long-term mean.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, it is expected that the trend of noise reduction will continue, e.g., by implementing the supercontinuum generation in an all-normal-dispersion regime, which is insensitive to the input pump noise delivering the enhanced shot-to-shot spectral coherence. [16][17][18][19][20] Meanwhile, with respect to the achieved average power, intensities up to 21.8 W were recently achieved in the wavelength range of 1.9-3.8 mm. 21 The broad spectral range covered by these sources is continuously extending [22][23][24][25][26][27] even beyond the fingerprint region revealing attractive potentials for spectroscopic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…With this technique repetition rates exceeding 100 kHz can be achieved [2,4]. Nevertheless, very few studies addressing temperature evaluation from the broadband spectra are currently found [3,5].…”
Section: Introductionmentioning
confidence: 99%